Correlated dynamics of water and amphiphilic molecules in thin Newton black films - Di Napoli, Solange Mariel (2010)
The dynamical properties of amphiphilics in Newton black films, as well as those of the water confined between the two charged hydrophilic surfaces, have been calculated via a series of molecular dynamic calculations in several films with different water content. A charged semi-flexible amphiphilic model and the TIP5P model of water are used in our simulations [J. Chem. Phys. 129, 164901 (2008)]. We calculate the diffusion coefficients, reorientational dynamics and the atomic density profile of water molecules as a function of the number of water molecules per amphiphilic (nw). We also analyse the reorientational motion of the amphiphilics and  determine a strong correlation between the dynamics of water molecules and the translational and reorientational dynamics of the amphiphilics, as well as a correlation between the reorientational dynamics of the amphiphilics belonging to the  upper and lower halves of the studied thin films.